Study on the Electronic Design Automation of Taximeter - Wang, Yuyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
The integration of Field Programmable Gate Arrays (FPGAs) into the design of digital taximeters signifies a transformative step forward in the field of Electronic Design Automation (EDA), catering to the evolving needs of urban transportation systems. This paper details the development and implementation of an FPGA-based digital taximeter that aims to enhance fare calculation accuracy, operational reliability, and adaptability to regulatory changes through the use of sophisticated technology. FPGAs are chosen for their ability to perform high-speed processing and to be reprogrammed in the field, which allows the taximeter system to adapt quickly to new fare structures and transportation regulations.